ANALISIS PERBANDINGAN IPv4 DENGAN IPv6 PENGGUNAAN CCTV BERBASIS AREA TRAFFICT CONTROL SECURITY (ATCS) - Mualfah, Desti; Putra, Gope Mandala; Firdaus, Rahmad (Jurnal Rekayasa Perangkat Lunak dan Sistem Informasi, 2022)
Internet access is an activity that cannot be separated from the needs of the community, it can be seen from the many activities that use TCP/IP-based internet access. The use of the internet protocol using IPv4 which is currently starting to not meet human needs, it is recommended to be able to implement IPv6 which has a simple header and has a better QoS (Quality of Service). One of these IPv6 is applied to traffic CCTV cameras based on ATCS (Area Traffic Control Security) which works to unify and record traffic activities for 24 hours in the hope that the video streaming results have better network quality.